PENGARUH PERUBAHAN TEGANGAN PRAKONSOLIDASI EFEKTIF (Ó’ C) PADA PENAMBAHAN KAPUR TERHADAP TANAH LEMPUNG - Novianto, Dandung; ., Supiyono (Media Teknik Sipil, 2012)
Dandung Novianto1 & Supiyono2ABSTRACTLand in the northern Karangploso a lot of clay and road conditions are not yet paved area slopes Arjuno especially so with much rain like this to go down to the sub-wheel motorcycle must be given chain. With the state’s basic research is done, by mixing soil with lime. Research made by mixing soil and chalk in the four comparisons. The first native land. Both the original soil mixed with chalk 5%. The third native soil mixed with chalk 7.5%. The four original soil mixed with chalk 10%. Each of these sought specific gravity, liquid limit, plastic limit and plasticity index on the original soil, mixing 5%, 7.5% and 10%. From the test results, can be summed up as follows: The preconsolidation pressure original land is 0.66. Mixing soil with chalk, the most optimal to raise the preconsolidation pressure is mixing 10%. The pressure value Preconsolidation the mixing of 10% is 2.5.Key Words : Chalk, Clay and Preconsolidation Pressure.